2017
DOI: 10.1002/slct.201701838
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium-Substituted Polyoxometalate Ionic Liquid Hybrids: Effect of Alkyl Chain on Dye Removal

Abstract: Vanadium substituted polyoxometalate ionic liquids (POM‐ILs) with increase in alkyl chain lengths, C4MImPV3W9O40, C8MImPV3W9O40, and C16MImPV3W9O40 were prepared by simple ion exchange method. These materials were characterized by elemental analysis, FTIR, electron microscopy, and thermal analysis. The dye removal ability towards methylene blue and methyl orange was studied under neutral pH. The dye removal rate of C4MImPV3W9O40 and C8MImPV3W9O40 towards methylene blue was 95%. The dye removal rate of C16MImPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…Dihydroxy compounds and ethyl acetoacetate were purchased from Avra chemicals and used as such without any purification. Methyl octyl imidazolium bromide, potassium trivanadophosphotungstate, methyl octyl imidazolium trivanadotungstate hybrid were prepared as per process given in the literature …”
Section: Methodsmentioning
confidence: 99%
“…Dihydroxy compounds and ethyl acetoacetate were purchased from Avra chemicals and used as such without any purification. Methyl octyl imidazolium bromide, potassium trivanadophosphotungstate, methyl octyl imidazolium trivanadotungstate hybrid were prepared as per process given in the literature …”
Section: Methodsmentioning
confidence: 99%
“…The most commonly used synthetic routes to fabricate water insoluble POMs as adsorbents in water treatment techniques are chemical precipitation, 53,54 sol− gel, 42 ultrasonication-assisted, 55,56 microwave-irradiated, 8,57 hydrothermal or solvothermal, 7,46 and ionothermal. 51,52 3. REMOVAL OF ORGANIC DYES USING POLYOXOMETALATE-BASED MATERIALS Organic dyes are hazardous water pollutants, which are discharged from many sources such as printing, textile, dyeing, paper and pulp, rubber, food, and paint industries.…”
Section: Synthesis and Assemblymentioning
confidence: 99%
“…In this regard, Yan et al 70 reported the use of POM@MOF composite (PW 11 V@MIL-101(Cr)) for removal of MO, and the adsorption efficiency was less than 19%, which was due to the adsorption of MO on the surface of the composites and the presence of highly electronegative POM loaded on the complex, which causes the reduced adsorption of MO on the surface of the complex. Later, a study by Mani et al 52 utilizing a series of vanadium-substituted POM-IL hybrids, aqueous solution of PBV through the column at a relatively high flow rate of 6 mL min −1 and POM-SILP offered 95% adsorption efficiency whereas 4% was recorded for the non-modified silica.…”
Section: Pom−ionic Liquid Hybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…Industrial organic dyes have remarkable applications in printing, textile, paint, pharmaceutical, cosmetic, food, etc., [1][2][3][4] however, as a hazardous side effect is producing a large amounts of wastewater as an environmental pollutant. [5,6] It is estimated that during the dyeing process in the textile industry, nearly 10%-15% of the dyestuffs were leaked into the aquatic environment, and their degradation is very difficult. [7][8][9] One of the very toxic azo dyes is Amido Black 10B, which may affect the human respiratory system and it can also cause skin and eye damages.…”
Section: Introductionmentioning
confidence: 99%